COVID-19: Reducing the risk of infection might increase the risk of intimate partner violence (2020)
The ongoing pandemic caused by SARS-CoV-2, the causal agent of the acute respiratory distress syndrome COVID-19, is placing unprecedented stress on healthcare systems and societies as a whole. The rapid spread of the virus in the absence of targeted therapies or a vaccine, is forcing countries to respond with strong preventative measures ranging from mitigation to containment. In extreme cases, quarantines are being imposed, limiting mobility to varying degrees. While quarantines are an effective measure of infection control, they can lead to significant social, economic and psychological consequences. Social distancing fosters isolation; exposes personal and collective vulnerabilities while limiting accessible and familiar support options. The inability to work has immediate economic repercussions and deprives many individuals of essential livelihoods and health care benefits. Psychological consequences may range from stress, frustration and anger to severe depression and post-traumatic stress disorder (PTSD). A recent review drawing on lessons from past pandemics shows the length of quarantine increases the risk for serious psychological consequences [1]. A relevant, yet frequently ignored risk during a pandemic and its socially disrupting response, is the potential increase of intimate partner violence.